Neurological Complications of Intrathecal Chemotherapy in Children: Experience in A Tertiary Care Hospital in Bangladesh - Sonia, Sheikh Farjana; Mishra, Avijeet Kumar; Sultana, Azmeri; Afroze, Sharmin (Dhaka Shishu (Children) Hospital Journal, 2022)
Background: Intrathecal (IT) chemotherapeutic agents have a narrow therapeutic index and high potential for toxicity. Though severe side effects are rare, but sometime consequences of IT chemotherapy can be catastrophic. Objectives: The objective of the study was to observe the neurological complications of intrathecal chemotherapy administrations in patients getting treatment for childhood malignancy. Methods: This prospective study included 33 patients who received IT chemotherapy on 76 occasions from July 2020 to December 2020 at Dr. M R Khan Shishu Hospital and ICH. We documented all the neurological complications within two weeks of IT chemotherapy. We defined minor neurological complications as headache, backache, fever, nausea, or vomiting. Major neurological complications were defined as nuchal rigidity, paresthesia, paralysis, or chemical arachnoiditis. All the cases were managed according to the internationally standard protocol. Results: Among the patients who received IT chemotherapy 64% were male and 36% were female. The mean age of child was 7 years. The most common diagnosis was BCP (B cell precursor) ALL (75.8%), followed by T-cell ALL (15.1%), APML (Acute promyelocytic leukemia) (6.1%), and B lymphoblastic Lymphoma (3%). Therapy consisted of methotrexate alone in 73 (96.1%) occasions, and cytarabine alone in 3(3.9%) occasions. Minor events occurred in 17(22.4%) occasions but no patient developed major events after administration of IT chemotherapy. Among the side effects a total of 5 (6.6%) occasions children developed nausea, 4 (5.3%) had back pain, 3 (3.9%) had headache, 2 had (2.6%) vomiting, 2 (2.6%) had dizziness and 1(1.3%) developed fever after IT chemotherapy administration. No patient developed major neurological events like neck rigidity, paralysis and chemical arachnoiditis. About 77.6% occasions, children did not develop any side effects after IT chemotherapy administration. Conclusion: No major toxic neurological events occurred but only minor neurological complications developed after IT chemotherapy administration. It is important for clinicians to be aware of the adverse events and consider them when treating patients with IT chemotherapy. DS (Child) H J 2021; 37(1): 15-20